Practice-Based Research Networks Ceding to a Single Institutional Review Board - Jeanette M. Daly; Tabria Weiner Harrod; Kate Judge; LeAnn C. Michaels; Barcey T. Levy; David L. Hahn; Lyle J. Fagnan; Donald E. Nease Jr. (Journal of Patient-Centered Research and Reviews, 2018)
Historically, a single research project involving numerous practice-based research networks (PBRNs) required multiple institutional review boards (IRBs) to be involved in approval of the project. However, to avoid redundancies, federal IRB regulations now allow cooperative research projects that involve more than one institution to use reasonable methods of cooperative IRB review and to cede authority for review and oversight of the project to a single lead IRB. Through ceding, a lead IRB has the authority for review and oversight of the project delegated by all participating sites’ IRBs and becomes the IRB of record for the ceded sites. In the conduct of cooperative research projects, each institution or primary care office site is still responsible for safeguarding the rights and welfare of human subjects and for complying with applicable regulations. The purpose of this report is to delineate the process, including cooperation and effort of personnel, for accomplishing IRB approval for the Implementing Networks’ Self-management Tools Through Engaging Patients and Practices (INSTTEPP) clinical trial. This process involved 4 PBRNs, 16 family physician offices, 4 academic institution’s IRBs, and 4 family practice office external IRBs ceding to the lead IRB. Once ceding was accomplished, subsequent IRB modifications and continuing reviews were the responsibility of the lead IRB, ultimately saving time for all participants and keeping the project on schedule.